Monitoring and Automatic Cooling Systems in Realtime Photovoltaic Based on IoT - Bambang Winardi; Agung Nugroho; Yosua Alvin (Indonesian Scientific Journal, 2022)
Monitoring the results of solar panel performance has an important role to evaluate the performance of solar panels in hot outdoor environmental conditions. This study aims to provide a new direct and real-time monitoring method for monitoring voltage, current, and temperature in solar panels and automatic cooling systems for solar panel surfaces. To meet these needs, a solar panel temperature monitoring and control system has been designed. This system is equipped with voltage sensors, current sensors, and temperature sensors, a data transfer system that is integrated in the smartphone application, automatic control of the cooling system on the panel, and cloud storage for Internet of Things (IoT)-based data. storage. The design of this system is based on the Arduino Uno microcontroller which is connected to Blynk IoT via the ESP8266 Wi-Fi module with serial communication so that the system can be controlled and monitored in real time. The results obtained from this monitoring system are measurement data for each sensor which can be directly stored and displayed on the Blynk application dashboard in real time. From the results of a comparison of testing the cooling system on the surface of the panel for application variation 2 with a setpoint of 35 °C, an average temperature drop of 8.79 °C or 21.1% is obtained and for variation 3 with a setpoint of 30 °C, the average temperature drop of 8.69 °C or 20.89% compared to without using a cooling system with an average temperature of 41.57 °C. So that the use of a cooling system with water flow is very useful for public knowledge in terms of lowering the temperature on the surface of the solar panel, so that it will increase the output of the solar panel.